2004
DOI: 10.21914/anziamj.v45i0.938
|View full text |Cite
|
Sign up to set email alerts
|

Influence of location, number and shape of corrugations in slider bearings

Abstract: The effects of location and shape of a localised corrugation on the performance of a fixed inclined slider bearing are investigated numerically, using a finite element method. It is shown that normal force increases uniformly as the corrugation is relocated downstream in the bearing gap, from being less than that of the smooth walled case to being higher, while flow rate decreases, also uniformly. Corrugation with the shape of rectangle waves produce largest changes in pressure distribution, normal force and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Using a commercial CFD code, Cupillard [18] investigated the effect of introducing a textured surface on the performance of a journal bearing and the mechanism of pressure buildup due to existence of textures in an inclined slider bearing. In addition, the influence of different surface corrugation shapes of triangular, sinusoidal and rectangular and their location on the performance of fixed inclined slider bearings has been studied by Huynh and Loe [19] under non-isothermal flow conditions utilising FEM. Of the three studied corrugation shapes, it was found that rectangle waves produce largest changes in the pressure distribution, normal force and flow rate relative to the smooth walled cases.…”
Section: Introductionmentioning
confidence: 99%
“…Using a commercial CFD code, Cupillard [18] investigated the effect of introducing a textured surface on the performance of a journal bearing and the mechanism of pressure buildup due to existence of textures in an inclined slider bearing. In addition, the influence of different surface corrugation shapes of triangular, sinusoidal and rectangular and their location on the performance of fixed inclined slider bearings has been studied by Huynh and Loe [19] under non-isothermal flow conditions utilising FEM. Of the three studied corrugation shapes, it was found that rectangle waves produce largest changes in the pressure distribution, normal force and flow rate relative to the smooth walled cases.…”
Section: Introductionmentioning
confidence: 99%